Locoregional recurrence after VATS surgery for NSCLC - Falcoz, Pierre-Emmanuel; Massard, Gilbert (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
In the present article, Doctor Haruki and associates (1) seek to address the very invigorating question of the distribution and prevalence of locoregional recurrence after video-assisted thoracoscopic surgery (VATS). This remarkable work not only contributes to a deeper understanding of the patterns of recurrence, but also questions some of the traditional and prominent surgical dogmas in the area of VATS lung resection for primary lung cancer.